2014
DOI: 10.1111/mec.12689
|View full text |Cite
|
Sign up to set email alerts
|

Climate, physiological tolerance and sex‐biased dispersal shape genetic structure of Neotropical orchid bees

Abstract: Understanding the impact of past climatic events on the demographic history of extant species is critical for predicting species' responses to future climate change. Palaeoclimatic instability is a major mechanism of lineage diversification in taxa with low dispersal and small geographical ranges in tropical ecosystems. However, the impact of these climatic events remains questionable for the diversification of species with high levels of gene flow and large geographical distributions. In this study, we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
51
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 68 publications
(73 reference statements)
8
51
1
Order By: Relevance
“…Less detailed studies have inferred similar patterns in the Southern Hemisphere [43], but few have examined how biota in tropical latitudes have responded to these global cycles [44,45]. The tropical Pacific represents a major driving force behind current global climates, and is expected to have played a considerable role throughout glacial periods [46].…”
Section: Discussionmentioning
confidence: 99%
“…Less detailed studies have inferred similar patterns in the Southern Hemisphere [43], but few have examined how biota in tropical latitudes have responded to these global cycles [44,45]. The tropical Pacific represents a major driving force behind current global climates, and is expected to have played a considerable role throughout glacial periods [46].…”
Section: Discussionmentioning
confidence: 99%
“…In all these studies, genetic analyses were based mainly on nuclear markers. However, when López-Uribe et al (2014) analysed the genetic diversity and population structure of three orchid bee species (Eulaema bombiformis , Eulaema meriana and Eulaema cingulata ) using both nuclear and mitochondrial markers, they detected discrepant results between the two types of markers regarding the structuring of populations of these species.…”
Section: Introductionmentioning
confidence: 92%
“…Thus, based on the recent findings of López-Uribe et al (2014), it seems logical to use a combination of nuclear and mitochondrial markers to achieve a better understanding of the genetic structure of Euglossini populations.…”
Section: Introductionmentioning
confidence: 98%
“…Two recent studies (Groom et al 2014a;López-Uribe et al 2014) have used phylogeographic and coalescent Bayesian Skyline Plot analyses to examine changes in bee abundances for tropical halictine (Halictidae) and euglossine (Apidae) bees respectively. Both studies found a strong response to Pleistocene climates, suggesting that these two faunal groups have been impacted by glacial cycles despite their tropical distribution.…”
Section: Introductionmentioning
confidence: 99%